Dietary Intervention Using Salacca (Snake Fruit) Chips to Combat Anemia in Pregnancy: Evaluation of Iron Status Improvement and Compliance Factors in Padangsidempuan, Indonesia - Elvi Suryani (International Journal of Public Health Excellence (IJPHE), 2026)
Anemia in pregnancy remains a critical public health challenge in Indonesia, with prevalence exceeding 48% in some regions. Conventional iron supplementation faces barriers related to adherence and side effects. Salacca zalacca (snake fruit), an indigenous Indonesian fruit rich in iron (3.9–4.2 mg), vitamin C (8.4 mg), and phytochemicals per 100 g, offers a promising food-based intervention. This study evaluated the efficacy of vacuum-fried snake fruit chips in improving iron status and assessed compliance determinants among anemic pregnant women in Padangsidempuan, North Sumatra. A quasi-experimental design involved 128 participants (64 per group). The intervention group received 50 g of snake fruit chips daily for 12 weeks plus routine iron–folic acid (IFA), while controls received IFA alone. At week 12, the intervention group showed significantly greater improvements in hemoglobin (11.82 ± 0.91 vs. 10.94 ± 1.02 g/dL), serum ferritin (28.46 ± 5.73 vs. 22.18 ± 6.41 μg/L), and hematocrit (35.86 ± 2.74% vs. 33.45 ± 3.12%) (all p < 0.001). Anemia prevalence reduction was 41.7% vs. 26.7% (p = 0.008). High compliance (≥80%) was achieved by 81.3% of the intervention group. Palatability, family support, and perceived health benefits were significant positive predictors of compliance. These findings support integrating culturally acceptable, food-based interventions into maternal nutrition programs to address iron deficiency anemia in resource-limited settings.